Investigation of technological parameters of guinea fowl, muscovy duck and turkey meat for the production of culinary products using sous-vide technology - A. M. Patieva; S. V. Patieva; Z. N. Khatko; T. B. Kolotiy; A. S. Shirokova (Новые технологии, 2025)
Introduction. The Russian poultry market is currently the most popular among consumers and a rapidly developing area that ensures food security for the country as a whole. Poultry products remain a familiar food for Russian consumers, which stabilizes consumer demand for this raw material. To meet people's needs and improve the diet, it is necessary to apply technologies using new raw materials. Unconventional types of raw materials with biological and increased nutritional value are one of the ways to expand the range of functional foods. Guinea fowl, musk duck and turkey meat can be attributed to these types of raw materials. High demand for poultry meat is explained by both its consumer properties and low consumer prices compared to other types of meat products.   The goal of the research is to study technological (mass-metric) indicators of guinea fowl, musk duck and turkey meat to create a line of culinary products using sous-vide technology.   Guinea fowl, musk duck and turkey meat, secondary slaughter products are the objects of the research.   The Methods. Technological properties of guinea fowl, muscovy ducks and turkeys were studied using generally accepted methods. The birds were weighed before slaughter. After slaughter and cooling to 12 °C, the carcasses and by-products of slaughter were weighed. To assess the quality indicators of guinea fowl, muscovy duck and turkey meat, the meat and broth were tasted.   The Results. The slaughter yield, the yield of boned guinea fowl, muscovy duck and turkey meat, the yield of by-products of slaughter were determined, and a tasting assessment of the meat and broth was carried out.   Conclusions. It was experimentally established that the slaughter yield of the guinea fowl carcass was 84.2 %, the slaughter yield of the muscovy duck carcass was 94.5%, and the slaughter yield of the turkey carcass was 95.8 %. The meat yield of guinea fowl, muscovy duck and turkey was higher than that of broiler chicken carcasses (75 %) and geese (70 %).